Issues and opportunities regarding the U.S. space program : a summary report of a workshop on national space policy - Byerly, Radford; Leshner, Richard B.; Whitney, Pamela L. (National Academies Press, 2004)
"Ever since the completion of the Apollo program, there has been a lack of consensus about the future of human spaceflight. The Columbia tragedy in February 2003 rekindled public debate about this question. In November 2003, the Space Studies Board and the Aeronautics and Space Engineering Board organized a workshop to explore aspects of the question, what should be the principal purpose, goals, and priorities of the U.S. civil space program? This report presents a factual summary of that workshop, which identified past lessons learned and guiding principles for the future of the civil space program. Seven broad themes emerged from the workshop, and these themes are highlighted in the report. The report also presents discussions of strategies for the human spaceflight program and guiding principles of and boundary conditions for a 21st century space policy"--Publisher's website.